Phylogenetic relationships of diurnal, phytotelm-breeding Melanophryniscus (Anura: Bufonidae) based on mitogenomic data - Pie, Marcio R.; Stroher, Patricia R.; Belmonte-Lopes, Ricardo; Bornschein, Marcos R. [UNESP]; Ribeiro, Luiz F.; Faircloth, Brant C.; McCormack, John E. (Elsevier B.V., 2017)
Melanophryniscus is a bufonid frog genus with a broad geographic distribution over southeastern South America. In recent years, several new species of Melanophryniscus have been discovered in southern Brazil showing a distinctive life-history strategy for the genus - breeding in phytotelmata - as well as a strong association with high-altitude regions. In this study, we use mitogenomic data to infer the phylogenetic relationships among diurnal, phytotelm-breeding Melanopluyniscus and to determine the timing of their divergence. We obtained the mitochondrial genomes (not including the control region) for eight individuals of Melanophryniscus representing all three described species (M. alipioi, M. milanoi, and M. xanthostomus), as well as some recently-discovered and potentially new species. Gene order was conserved in all species and corresponded to the general order found in bufonids. Although the phylogenetic relationships among the studied species was poorly supported, dating confirmed that they diverged during the Pleistocene, suggesting that phytotelm breeding could have arisen during drier periods in the glacial/interglacial cycles due to a decrease in the availability of permanent streams or ephemeral/temporary streams or ponds in which Melanophryniscus species commonly breed.
Keywords: Red-belly toads; Atlantic Forest; Mitochondrial DNA; Montane anurans